Evolution of robot‐assisted orthotopic ileal neobladder formation: a step‐by‐step update to the University of Southern California (USC) technique. (18th October 2016) - Chopra, Sameer; de Castro Abreu, Andre Luis; Berger, Andre K.; Sehgal, Shuchi; Gill, Inderbir; Aron, Monish; Desai, Mihir M.
Abstract : Objective: To describe our, step‐by‐step, technique for robotic intracorporeal neobladder formation. Patients and Methods: The main surgical steps to forming the intracorporeal orthotopic ileal neobladder are: isolation of 65 cm of small bowel; small bowel anastomosis; bowel detubularisation; suture of the posterior wall of the neobladder; neobladder–urethral anastomosis and cross folding of the pouch; and uretero‐enteral anastomosis. Improvements have been made to these steps to enhance time efficiency without compromising neobladder configuration. Results: Our technical improvements have resulted in an improvement in operative time from 450 to 360 min. Conclusion: We describe an updated step‐by‐step technique of robot‐assisted intracorporeal orthotopic ileal neobladder formation.